Critical Race Theory and Education - Cole, M. author. aut Link
XV, 212 p.
Keywords: Critical Race Theory (CRT) in the realm of Education has a long history in the US, and is now a bourgeoning field of enquiry in the UK. Critical Race Theory and Education is the first book-length response to CRT from a Marxist perspective. It looks at CRT's origins in Critical Legal Studies, critiques the work of major US and UK Critical Race Theorists and also looks at some of CRT's strengths. CRT and Marxism are contextualized with respect to both neo-liberal global capitalism and imperialism and to antiracist socialist developments in South America. The book concludes with some suggestions for classroom practice.